STUDI KITAB TAFSIR MAFATIH AL-GHAIB KARYA AR-RAZI - Ulil Azmi (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2022)
Ar-Razi was a scholar who dedicated his life to science. Ar-Razi's scientific journey has led him to become a scholar who masters various disciplines as evidenced by his works. This article discusses one of ar-Razi's great works in the field of interpretation, Mafatih al-Ghaib. This book of interpretations is classified as a commendable interpretation of bi al-ra’y. Extensive discussion makes this book one of the references to the interpretation of the Quran to this day. The use of the tahlili method makes ar-Razi's work have a comprehensive discussion. This book of interpretation reviews various aspects, such as the study of the Quranic science and other scientific disciplines. His steadfastness in defending the ahl al-sunnah is also evident in his work in addition to the fiqh discussions he presents. As a result, there was a lot of praise for this book of interpretation in addition to the criticism given. Therefore, it is necessary to describe this magnum opus ar-Razi so that it is known by people, especially interpreters.